Pencegahan Resiko Alergi Berupa Asma Bronkial & Dermatitis Atopik Pada Masyarakat Terhadap Keberadaan Tungau Debu Rumah - Zahara Fadilla; Aulia Mutiara Hikmah; Laili Safitri; Anisyah Octaviyanti (Jurnal Pengabdian Ilmu Kesehatan, 2023)
House dust mites ( are household allergens spread throughout the world associated with manifestations of allergic symptoms in the respiratory tract (bronchial asthma) and skin (atopic dermatitis). Prevention of allergic risks of bronchial asthma and atopic dermatitis can be done by cleaning the house from dust. The purpose of community service is to increase public knowledge and understanding to prevent the risk of allergic asthma and atopic dermatitis. The method used in the implementation of community service is to socialize with the community, the assessment of increasing community knowledge is carried out by conducting a pretest and posttest. The results of outreach to community service participants showed that there was an increase in participants' knowledge regarding prevention of allergies in the form of bronchial asthma and atopic dermatitis against house dust mite infection (TDR).